Management of Priapism: Results of a Nationwide Survey and Comparison with International Guidelines - Kalkanli, Arif; Sonmez, Salih Zeki; Guvel, Mine; Aglamis, Erdogan; Araz, Seyhmuz; Asfuroglu, Ahmet; Kadioglu, Ates (Aves, 2023)
Objective: The aim of this study is to evaluate current urologic practice regarding the management of priapism in Turkey and compare with international guidelines. Methods: Urologists and urology residents were invited to an online survey consisting of 30 multiple-choice questions on priapism-related clinical practices that were considered most important and relevant to practices by using Google Forms. Results: Total number of responses was 340. Respondents reported that they recorded a detailed patient's medical history and physical examination findings (n = 340, 100%) and laboratory testing, which includes corporal blood gas analysis (n = 323, 95%). Participants announced that they performed Doppler ultrasound for 1/4 cases (n = 106, 31%), but 22% of the participants (n = 75) replied that they performed in >75% of cases. Participants (n = 311, 91%) responded that the first-line treatment of ischemic priapism is decompression of the corpus cavernosum. Moreover, most respondents (n = 320, 94%) stated that sympathomimetic injection drugs should be applied as the second step. About three-quarters of respondents (n = 247, 73%) indicated adrenaline as their drug of choice. Phosphodiesterase type 5 inhibitors seems to be the most preferred drug for stuttering priapism (n = 141, 41%). Participants (n = 284, 84%) replied that corpora-glanular shunts should be preferred as the first. A large number of participants (n = 239, 70%) declared that magnetic resonance imaging can be performed in cases with delayed (>24 hours) priapism to diagnose corporal necrosis. Most of the participants (84%) responded that penile prosthesis should be preferred to shunts in cases with delayed (>48 hours) priapism. Conclusion: It would be appropriate to improve the training offered by professional associations and to give more training time to the management of priapism during residency.
Keywords: Priapism; andrology; penile prosthesis